Telecosteño: Constructing a linguistic imaginary in popular Colombian soap operas. (June 2022) - Quinn, Padraic Michael
Abstract: Linguistically, Colombia is divided into two macrovarieties of Spanish: cachaco (interior of the country) and costeño (from the coastal regions). This linguistic dichotomy can also be extended to the cultural ambit, with costeño varieties being negatively perceived in the Colombian sociolinguistic imaginary, which is in turn reflected in popular folk discourse on language. Thus, the present article explores how authenticity of the costeño macrodialect is constructed in Colombian telenovelas 'soap operas', examining the significance of the language ideologies behind these constructions. Data is presented from a corpus of popular telenovelas, with findings showing that the depiction of this diverse macro-variety is often 'exaggerated' or 'inauthentic', supporting popular suggestions of misrepresentation, as well as previous findings on a cachaco narration of the Other. Importantly, this reflects wider sentiment toward costeño varieties in terms of how deeply engrained language ideologies are manifested within the country, shedding light on the social structures behind these ideologies, contributing to studies on the role of popular media in constructing and perpetuating ideologies on variation.